Enhancing Learning Outcomes in Islamic Cultural History Using the Think-Talk-Write Model - Umami, Halida; Azmil, Rosidah; Firmansah, Defi (Nusantara Education, 2025)
The history of Islamic civilization is a subject designed to deepen sthe faith of elementary school students at the 'MI' (Madrasah Ibtidaiyah) level, emphasizing the cultivation of piety. Despite its focus on the history of Islamic civilization, many students face challenges in grasping the material, leading to subpar learning outcomes. This is largely due to their limited understanding of Islamic cultural history. The lack of diverse teaching models employed by teachers contributes to a monotonous and unengaging learning experience.This research is a qualitative descriptive approach based on the classroom action research method by Stephen Kemmis and Robyn McTaggart, the research involved 24 students, employing data collection methods such as observation, tests, documentation, and interviews.The results indicate the effectiveness of the Think Talk Write (TTW) Cooperative Learning model in improving both learning outcomes and student engagement. In the initial cycle, the learning outcomes percentage was 25%, which significantly rose to 91.67% in the subsequent cycle. Similarly, students' activeness increased from 50.41% in the first cycle to 89.58% in the second cycle.Based on these findings, it is recommended that teachers adopt cooperative learning models like Think Talk Write to enhance student engagement and learning outcomes